Contamination after disinfectant rectal washout in left colectomy as a model for transrectal NOTES: a randomized controlled trial - Müller, Philip C.; Steinemann, Daniel; Senft, Jonas; Gehrig, Tobias; Benner, Laura; Nickel, Felix; Müller, Beat P.; Linke, Georg R. (Journal of surgical research, 2018)
Background - In natural orifice transluminal endoscopic surgery (NOTES) with transrectal (TR) access the intraoperative opening of the rectal wall poses a risk of intraperitoneal contamination and subsequent infectious complications. A rectal washout with a disinfectant may reduce this risk. The aim of the study was to assess the intraoperative contamination on the circular stapler pin when a rectal washout with povidone-iodine (RW-PI) or Ringer solution was performed in patients undergoing left-sided colectomy. Furthermore, the additional effect of an irrigation instrument on the contamination was evaluated. - Methods - In a patient and assessor blinded randomized controlled trial, patients undergoing left-sided colectomy were assigned to rectal washout with PI with an irrigation instrument (RW-PI; n = 23), rectal washout with Ringer solution with an irrigation instrument (RW-R; n = 21) or rectal washout with Ringer solution without an irrigation instrument (RW; n = 25). An end-to-end anastomosis with a circular stapler was performed. The contamination on the pin of the circular stapler was chosen as primary endpoint in order to simulate the intraabdominal contamination risk during TR NOTES. Secondary endpoints were contamination of the rectal mucosa, peritoneal contamination and postoperative morbidity. - Results - The contamination rate of the pin of the circular stapler did not differ (RW-PI 39.1%, RW-R 33.3%, RW 52.0%; P = 0.421), but contamination of the rectal mucosa was reduced (47.8% versus 95.2% versus 100%; P < 0.001) and peritoneal contamination tended to be reduced (39.1% versus 71.4% versus 60.0%; P = 0.09) when a rectal washout with PI was performed. The rates of infectious complications (17.4% versus 9.5% versus 12.0%; P = 0.821) and of overall complications (30.4% versus 28.6% versus 44.0%; P = 0.476) did not differ. - Conclusions - Despite an intense rectal washout with PI, contamination of the stapler pin did not differ. Intraabdominal bacterial translocation was frequently encountered even after disinfectant rectal washout with PI. Further studies might focus on the clinical impact of intraabdominal contamination in TR NOTES.
Gesehen am 17.05.2019